1996
DOI: 10.1182/blood.v87.10.4455.bloodjournal87104455
|View full text |Cite
|
Sign up to set email alerts
|

High resolution HLA matching associated with decreased mortality after unrelated bone marrow transplantation

Abstract: As compared with related HLA-identical sibling donors, bone marrow transplantation (BMT) with phenotypically HLA ABDR-compatible unrelated donors is associated with increased mortality. This may be due to hidden HLA incompatibilities not detected by conventional typing. We have analyzed 44 unrelated patient-donor pairs who were matched for HLA- A, -B, and -DR by routine tissue typing. Our comprehensive HLA typing approach consisted of serology, cytotoxic T-cell precursor (CTLp) tests, T-cell cloning, oligotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…All the remaining HLA-A, -B, -C, -DRB1/ B3/B5 and -DQB1 antigens (not shown) were matched between patient and donor. The complete list of patient and donor HLA antigens is published elsewhere (Speiser et al, 1996). association with oligotyping for HLA class II antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the remaining HLA-A, -B, -C, -DRB1/ B3/B5 and -DQB1 antigens (not shown) were matched between patient and donor. The complete list of patient and donor HLA antigens is published elsewhere (Speiser et al, 1996). association with oligotyping for HLA class II antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Their diagnoses were CML, MDS and histiocytosis. The table of all the histocompatibility antigens of the 44 patients is published elsewhere in a report analysing the association between comprehensive HLA matching and clinical results (Speiser et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Other explanations could also accotmt for discrepancies between the results of in vitro assays and clinical outcome. Antigens which generate a CTL response might not evoke GVHD because of inappropriate tissue distribution in vivo, low T-cell receptor afRnity which might be sufficient to generate a response in vitro but not in vivo (56), or an inadequate helper T-cell response in vivo (57). Likewise, antigens which generate HTL responses might not evoke GVHD in the absence of a CTL response (58).…”
Section: Functional Assays For Assessing Histocompatibilitymentioning
confidence: 99%
“…1 Currently, matching at HLA-A, HLA-B, HLA-C, HLA-DRB1, and DQB1 (10/10) is considered optimal, with a single mismatch at any non-DQB1 allele associated with 5%-10% increase in mortality and/or significant GVHD, whereas DQB1 mismatches are thought to be better tolerated. [2][3][4][5][6][7][8][9][10] Recent literature has suggested that matching at the HLA-DPB1 locus, in addition to the standard loci, may impact outcomes in ASCT. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The β-chain of the HLA-DP antigen is known to be highly polymorphic, with 716 alleles encoding 591 proteins and 19 null variants, while the α-chain has 44 alleles encoding 22 proteins.…”
Section: Introductionmentioning
confidence: 99%